ANALYSIS OF TYPE IMPROVEMENT IN SIDOMUKTI SUB DISTRICT OF SALATIGA CITY OF CENTRAL JAVA PROVINCE - Novaria, Rachmawati; Suwardi, Suwardi; Sugiyarti, Sri Riris; Sadono, Teguh Priyo (Dinamika Governance : Jurnal Ilmu Administrasi Negara, 2021)
Abstract Salatiga City Government has four sub-districts. Three sub-districts already received type A: Sidorejo, Argomulyo, and Tingkir. But, the Sidomukti sub-district is still typed B. The city continues to grow and needs to improve its services. Sidomukti sub-district needs to be upgraded to type-A so that services become more effective. This study is intended to produce an analysis of how to increase the sub-district status to type - A. The research uses a descriptive-analytic method with a formal legal approach. The results show that the general variable score is 100 (one hundred), and the unique variable score is 440 (four hundred and forty). The overall score is 540 (five hundred and forty). The conclusion of the study still places Sidomukti District in the type B sub-district. Regarding PP 18 of 2016 concerning Regional Apparatus for type A sub-district, the minimum score is above 600. This research recommendation proposes a regional expansion to achieve an increase in score of 610. Keyword: Upgrade, sub-district, Sidomukti, Salatiga Intisari Pemerintah Kota Salatiga memiliki empat kecamatan. Tiga kecamatan tipe A: Sidorejo, Argomulyo dan Tingkir. Kecamatan Sidomukti masih bertipe B. Kota terus bertumbuh butuh meningkatkan pelayanan. Kecamatan Sidomukti perlu ditingkatkan statusnya menjadi tipe –A agar pelayanan menjadi lebih efektif. Penelitian ini dimaksudkan untuk menghasilkan analisis peningkatan status kecamatan menjadi tipe – A. Penelitian menggunakan metode  deskriptif analitik dengan pendekatan legal formal. Hasil penelitian menunjukan skor variabel umum sejumlah 100 (seratus) dan skor variabel khusus  440 (empat ratus empat puluh). Keseluruhan skor diperoleh 540 (lima ratus empat puluh). Kesimpulan penelitian masih menempatkan Kecamatan Sidomukti berada pada kecamatan tipe B. Merujuk pada PP 18 Tahun 2016 tentang Perangkat Daerah untuk tipe kecamatan dengan tipe A maka skor minimal adalah diatas 600. Rekomendasi penelitian ini mengusulkan pemekaran wilayah guna mencapai peningkatan skor 610. Kata Kunci: Tipe kecamatan, Sidomukti, Salatiga DOI : https://doi.org/10.33005/jdg.v11i2.2804